Dual-energy CT imaging of thoracic malignancies - Zhang, Long Jiang (e-Med, 2013)
Computed tomography (CT) plays a pivotal role in the detection, characterization, and staging of lung cancer and other thoracic malignancies. Since the introduction of clinically viable dual-energy CT techniques, substantial evidence has accumulated on the use of this modality for imaging chest malignancies. This article describes the principles of dual-energy CT along with suitable image acquisition, reconstruction, and postprocessing strategies for oncologic applications in the chest. The potential of dual-energy CT techniques for the detection, characterization, staging, and surveillance of chest malignancy, as well as the limitations of this modality are discussed.